Risk factor for phlebitis in a patient with peripheral intravenous catheters: a cohort study - Eka Vivtin Agustiani; Agus Santosa (UM Purwokerto Press, 2020)
Phlebitis is one of nosocomial infections that frequently occurred in hospitals. Phlebitis is mainly related with infusion and therapy. Many risk factors can cause phlebitis. The purpose of this study was to predict the prevalence of phlebitis in patients based on the causal factors in Banyumas Regional Hospital. The design of this study was an analytic survey of cohort approach, with a sample of 218 by using consecutive sampling. The study was conducted from November to December 2019 using checklist of observation sheets. The results demonstrates 5 phlebitis risk factors associated with the occurrence of phlebitis, namely the type of fluid (P = 0.011), nutritional status (P = 0.001), catheter size (P = 0.002), injection therapy (P = 0.027) and comorbidities (P = 0.003). The probability of 5 risk factors for the occurrence of phlebitis (88.28%) with nutritional status being the dominant factor (b = 3.928) with probability of (13.48%). To minimize the prevalence of phlebitis, the medical personnel may conduct initial phlebitis screening to determine accurate and appropriate preventive measures.